1962
DOI: 10.1152/ajplegacy.1962.202.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to insulin in the absence of hypoglycemia

Abstract: Cardiovascular responses to intravenous administration of insulin were studied in lightly anesthetized dogs treated with a neuromuscular blocking agent. An early transient pressor response was observed. This abrupt increase in arterial pressure appeared 2–9 min after insulin was given. It was accompanied by increases in cardiac output and right atrial pressure. It occurred in the presence of hyperglycemia and in the absence of hypoglycemia. It was not altered by glucagon but it could be antagonized by ganglion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

1966
1966
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 0 publications
2
43
0
Order By: Relevance
“…In this regard, an earlier study found a small but significant decrease in diastolic blood pressure during insulin/glucose infusion in humans (6). Alternatively, a central neural action of insulin may also contribute to stimulation of sympathetic outflow in this setting (8,(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, an earlier study found a small but significant decrease in diastolic blood pressure during insulin/glucose infusion in humans (6). Alternatively, a central neural action of insulin may also contribute to stimulation of sympathetic outflow in this setting (8,(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 94%
“…Insulin-specific binding sites have been located in the hypothalamus of the rat brain (25), and intraventricular injections of insulin have been shown to increase CNS catecholamine turn-2250 over (26). Pereda et al (27) have shown that infusing insulin into the carotid arteries of dogs, at doses which have no effect when administered systematically, elevate arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In an early study, a low dose of insulin injected into the carotid arteries of dogs increased blood pressure before a fall in blood glucose (27). A relationship between insulin sensitive regions in the hypothalamus and sympathetic activity was later established in experiments using gold thioglucose in mice (28).…”
Section: Direct Neural Mechanismsmentioning
confidence: 99%